S100A9-Imaging Enables Estimation of Early Therapy-Mediated Changes in the Inflammatory Tumor Microenvironment - Anne Helfen; Annika Schnepel; Jan Rieß; Miriam Stölting; Mirjam Gerwing; Max Masthoff; Thomas Vogl; Johannes Roth; Carsten Höltke; Moritz Wildgruber; Michel Eisenblätter (Biomedicines, 2021)
(1) Background: The prognosis of cancer is dependent on immune cells in the tumor microenvironment (TME). The protein S100A9 is an essential regulator of the TME, associated with poor prognosis. In this study, we evaluated early therapy effects on the TME in syngeneic murine breast cancer via S100A9-specific in vivo imaging. (2) Methods: Murine 4T1 cells were implanted orthotopically in female BALB/c mice (n = 59). Tumor size-adapted fluorescence imaging was performed before and 5 days after chemo- (Doxorubicin, n = 20), anti-angiogenic therapy (Bevacizumab, n = 20), or placebo (NaCl, n = 19). Imaging results were validated ex vivo (immunohistochemistry, flow cytometry). (3) Results: While tumor growth revealed no differences (p = 0.48), fluorescence intensities (FI) for S100A9 in Bevacizumab-treated tumors were significantly lower as compared to Doxorubicin (2.60 vs. 15.65 AU, p < 0.0001). FI for Doxorubicin were significantly higher compared to placebo (8.95 AU, p = 0.01). Flow cytometry revealed shifts in monocytic and T-cell cell infiltrates under therapy, correlating with imaging. (4) Conclusions: S100A9-specific imaging enables early detection of therapy effects visualizing immune cell activity in the TME, even before clinically detectable changes in tumor size. Therefore, it may serve as a non-invasive imaging biomarker for early therapy effects.